Composite brazing filler metal for brazing Ti2AlNb alloy and high-nitrogen steel and brazing method

Through the powdering treatment prepared by using composite brazing materials and vacuum atomization method, combined with the technical means of laying Ti powder during the brazing process, the problems of low welding strength and nitrogen loss of Ti2AlNb and high nitrogen steels were solved, and the strength and quality improvement of the welding interface were achieved.

CN119609458AActive Publication Date: 2025-03-14CITIC HEAVY INDUSTRIES CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510164438.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The welding between Ti2AlNb and high nitrogen steel has problems such as low strength, large differences in chemical and physical properties, differences in thermal expansion coefficients lead to residual stress, poor mutual solubility lead to the formation of brittle hard intermetallic compounds, and nitrogen element precipitation lead to the air clamping defect.

Method used

The composite solder material, Zr2Ni alloy powder with a mass percentage of 20~30%, Zr2Cu alloy powder and residual Ti powder were prepared by vacuum atomization method, and the Ti powder was laid on the side of high-nitrogen steel during the brazing process, and Ti elements were used to generate TiN reinforced phases, prevent the diffusion of Fe elements and inhibit the formation of brittle intermetallic compounds.

Benefits of technology

The strength of the Ti2AlNb/high nitrogen steel welding interface was improved, the problems of nitrogen element loss and brittle hard phase defects were overcome, and the welding quality was significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609458A_ABST
    Figure CN119609458A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of brazing materials, and particularly discloses composite brazing filler metal for brazing Ti2AlNb alloy and high-nitrogen steel and a brazing method. The composite brazing filler metal is composed of, by mass, 20%-30% of Zr2Ni alloy powder, 20%-30% of Zr2Cu alloy powder and the balance Ti powder. The brazing method comprises the steps that base metal is pretreated; ti powder is flatly laid on the to-be-brazed face of the high-nitrogen steel base metal, the to-be-brazed face of the Ti2AlNb alloy base metal is coated with paste brazing filler metal, and the Ti2AlNb alloy base metal and the high-nitrogen steel base metal are oppositely attached to obtain a pre-brazed assembly; and the pre-brazing assembly is placed in a vacuum brazing furnace to be subjected to brazing treatment. According to the composite brazing filler metal, the alloy components and the Ti powder are laid and assembled respectively, most of Ti elements are controlled on the steel side through the preferentially-laid Ti powder, the Ti elements participate in formation of N compounds in high-nitrogen steel, the N elements in the high-nitrogen steel can be fixed through Ti, a TiN strengthening phase is generated, grains of a phase structure are refined, and the strength of a welding interface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing materials, and in particular to a composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel and a brazing method. Background Art

[0002] Ti2AlNb alloy has the advantages of low density, high corrosion resistance, high temperature strength, high oxidation resistance, excellent creep resistance and stable microstructure. It is an ideal material to replace nickel-based high-temperature alloys in turbocharger manufacturing. High nitrogen steel is a new type of stainless steel that is currently booming. It has high strength, high toughness, large creep resistance and good corrosion resistance. It is suitable for materials for aircraft engine shaft end components and turbocharger rotor shafts. Reliable connection of Ti2AlNb and high nitrogen steel not only solves the inherent difficult processing problem of Ti2AlNb intermetallic compounds, but also significantly improves energy conversion efficiency and transient response capabilities while reducing weight. However, there are great differences in chemical and physical properties between Ti2AlNb and high nitrogen steel dissimilar metals, making welding the two extremely difficult. The main reasons include: 1. Ti2AlNb and high nitrogen steel are metal heterogeneous connections, and the difference in thermal expansion coefficients is too large, so the brazed joint will produce large residual stress and cause cracking; 2. High nitrogen steel and Ti2AlNb have poor solubility, and brittle and hard intermetallic compounds are easily generated during the welding process, weakening the interface bonding strength; 3. The precipitation of nitrogen in high nitrogen steel causes defects such as air inclusion and the formation of brittle and hard phases, reducing the quality of the joint. Summary of the invention

[0003] The purpose of the present invention is to solve the technical problem of low welding strength of Ti2AlNb and high nitrogen steel, and to provide a composite brazing filler metal and a brazing method for brazing Ti2AlNb alloy and high nitrogen steel.

[0004] In order to solve the deficiencies of the above technical problems, the technical solution adopted by the present invention is: a composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel, wherein the composite brazing filler metal is composed of 20-30% Zr2Ni alloy powder, 20-30% Zr2Cu alloy powder and the remainder Ti powder in terms of mass percentage.

[0005] As a further optimization of the composite brazing material for brazing Ti2AlNb alloy and high nitrogen steel of the present invention: the particle sizes of the Zr2Ni alloy powder, Zr2Cu alloy powder and Ti powder are all 10-50 μm.

[0006] As a further optimization of the composite brazing material for brazing Ti2AlNb alloy and high nitrogen steel of the present invention: the preparation method of the Zr2Ni alloy powder and the Zr2Cu alloy powder is as follows:

[0007] The alloy foil strip is vacuum melted in an argon atmosphere to obtain an alloy ingot.

[0008] The alloy ingot is subjected to amorphous forming treatment by a single-roller strip spinning method to obtain amorphous foil brazing material.

[0009] The amorphous foil solder is powdered by vacuum atomization.

[0010] As a further optimization of the composite brazing material for brazing Ti2AlNb alloy and high nitrogen steel of the present invention: the vacuum atomization method is specifically as follows:

[0011] The amorphous foil brazing material was crushed and placed in a quartz tube and evacuated to 1×10 -1 MPa and filled with argon.

[0012] Arc melting is performed until the foil in the quartz tube is completely melted to form a refined melt.

[0013] The refined melt is solidified into particles in the atomizing tower through a gas nozzle and then sorted through a cyclone separator.

[0014] As a further optimization of the composite brazing material for brazing Ti2AlNb alloy and high nitrogen steel of the present invention: the diameter of the gas nozzle is 5 mm, the diameter of the atomizing nozzle is 1 mm, the atomizing time is 15-20 min, and the vacuum leakage rate of the atomizing tower is 0.5-0.6 Pa / h.

[0015] The present invention also provides a brazing method for Ti2AlNb alloy and high nitrogen steel, comprising the following steps:

[0016] S1: Pretreatment of Ti2AlNb alloy base material and high nitrogen steel base material.

[0017] S2: Spread the Ti powder in the composite solder on the surface to be welded of the high nitrogen steel base material, apply paste solder on the surface to be welded of the Ti2AlNb alloy base material, and fit the surfaces to be welded of the Ti2AlNb alloy base material and the high nitrogen steel base material relatively to obtain a pre-brazed assembly.

[0018] The paste solder is a mixture of Zr2Ni alloy powder, Zr2Cu alloy powder and a binder.

[0019] S3: Place the pre-brazed assembly in a vacuum brazing furnace at a vacuum degree of 1.0×10 -3 Pa, heat to 300-500°C at a heating rate of 10°C / min-30°C / min and keep warm for 5-10 min, then heat to brazing temperature at a heating rate of 15°C / min and keep warm for 10-15 min for brazing. After brazing, cool to room temperature with the furnace to complete the brazing connection of Ti2AlNb alloy and high nitrogen steel.

[0020] As a further optimization of the brazing method of a Ti2AlNb alloy and a high nitrogen steel of the present invention: the step S1 is specifically: the welding surfaces of the high nitrogen steel base material and the Ti2AlNb alloy base material are polished with 400#, 900# and 1500# sandpapers in turn, and then the polished base materials are immersed in acetone for ultrasonic cleaning for 8min to 12min, and finally rinsed with anhydrous ethanol and air-dried.

[0021] As a further optimization of the brazing method of Ti2AlNb alloy and high nitrogen steel of the present invention: in the step S2, the thickness of the Ti powder laid on the to-be-welded surface of the high nitrogen steel base material is 10-50 μm.

[0022] As a further optimization of the brazing method of a Ti2AlNb alloy and a high nitrogen steel of the present invention: the volume ratio of the composite brazing material to the binder in the paste brazing material is 9:1.

[0023] As a further optimization of the brazing method of Ti2AlNb alloy and high nitrogen steel of the present invention: the brazing temperature in step S3 is 920°C-960°C.

[0024] The present invention has the following beneficial effects:

[0025] 1. The alloy components and Ti powder in the composite solder of the present invention are laid and assembled separately. The Ti powder laid first controls most of the Ti element on the steel side, so that it participates in the formation of N compounds in high nitrogen steel. On the one hand, Ti can fix the N element in high nitrogen steel, generate TiN strengthening phase, and then refine the grains of the phase structure, improve the strength of the connection interface, and overcome the problem of nitrogen loss in high nitrogen steel welding. On the other hand, the TiN continuous strengthening phase layer generated preferentially on the steel side can prevent the Fe element from diffusing into the brazing seam and inhibit the formation of FeTi brittle intermetallic compounds.

[0026] 2. In the brazing method of the present invention, the Ti element in the Ti2AlNb base material will diffuse into the brazing seam as the temperature rises. The diffused Ti is equivalent to the supplement of the laid Ti, which can accelerate the formation of a continuous TiN strengthening phase on the steel side. Therefore, the composite brazing material of the present invention is particularly suitable for the brazing connection of Ti2AlNb / high nitrogen steel in the shaft end parts of aircraft engines and the rotor shaft of turbochargers. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a microscopic morphology of the composite solder of Example 1; Figure 2 is the DSC curve diagram of the composite solder of Example 1; Figure 3 This is the brazing seam organization diagram of Example 1; Figure 4It is the shear fracture surface diagram (steel side) of the brazing joint of Ti2AlNb / high nitrogen steel in Example 1. Detailed implementation manners

[0028] To better understand the present invention, the content of the present invention will be further clarified below in conjunction with embodiments. However, the content of the present invention is not limited to the following embodiments.

[0029] <Composite filler metal for brazing Ti2AlNb alloy and high nitrogen steel> The composite filler metal is composed of 20-30% by mass of Zr2Ni alloy powder, 20-30% by mass of Zr2Cu alloy powder, and the balance of Ti powder.

[0030] Among them, the particle sizes of the Zr2Ni alloy powder, Zr2Cu alloy powder, and Ti powder are all 10-50 μm.

[0031] The preparation methods of the Zr2Ni alloy powder and the Zr2Cu alloy powder are as follows: The alloy foil strip is subjected to vacuum melting in an argon atmosphere to obtain an alloy ingot; The alloy ingot is subjected to amorphous forming treatment by the single-roll melt spinning method to obtain an amorphous foil strip filler metal; The amorphous foil strip filler metal is subjected to powdering treatment by the vacuum atomization method.

[0032] The above preparation method is a common preparation method in the prior art. Therefore, it will not be described in detail.

[0033] It should be noted that the vacuum atomization method is specifically: The amorphous foil strip filler metal is broken and placed in a quartz tube, and the vacuum is pumped to 1×10 -1 MPa and argon is filled; Arc melting is used to heat until the foil strip in the quartz tube is completely melted to form a refined melt; The refined melt is solidified in an atomization tower through a gas nozzle and then sorted by a cyclone separator.

[0034] The diameter of the gas nozzle is 5 mm, the diameter of the atomization nozzle is 1 mm, the atomization time is 15-20 min, and the vacuum leakage rate of the atomization tower is 0.5-0.6 Pa / h.

[0035] The vacuum atomization process is a modern processing method that does not change the mechanical properties and structure of the alloy, and can retain the characteristics of uniform chemical composition, good wettability, and good toughness of the amorphous alloy.

[0036] <Brazing process of Ti2AlNb alloy and high nitrogen steel> The brazing process includes the following steps: S1: Pretreat the Ti2AlNb alloy base material and the high nitrogen steel base material.

[0037] The pretreatment is as follows: the welding surfaces of the high nitrogen steel base material and the Ti2AlNb alloy base material are polished with 400#, 900# and 1500# sandpapers in turn, and then the polished base materials are immersed in acetone for ultrasonic cleaning for 8min to 12min, and finally rinsed with anhydrous ethanol and air-dried.

[0038] S2: Spread the Ti powder in the composite solder on the surface to be welded of the high nitrogen steel base material (the thickness of the Ti powder is 10-50 μm), apply paste solder on the surface to be welded of the Ti2AlNb alloy base material, and fit the Ti2AlNb alloy base material and the surface to be welded of the high nitrogen steel base material relatively to obtain a pre-brazed assembly.

[0039] The volume ratio of the alloy powder to the binder in the paste solder is 9:1, and the alloy powder is the Zr2Ni alloy powder and the Zr2Cu alloy powder in the composite solder.

[0040] S3: Place the pre-brazed assembly in a vacuum brazing furnace and control the vacuum degree to 1.0×10 -3 Pa, heat up to 300-500℃ at a heating rate of 10℃ / min-30℃ / min and keep warm for 5-10min, then heat up to brazing temperature (920℃-960℃) at a heating rate of 15℃ / min and keep warm for 10-15min for brazing. After brazing, cool to room temperature with the furnace to complete the brazing connection of Ti2AlNb alloy and high nitrogen steel.

[0041] The high strength, high toughness, non-magnetic, corrosion resistance, and wear resistance of high nitrogen steel are all attributed to the presence of solid solution nitrogen in the parent material. Therefore, the mechanical properties and corrosion resistance of high nitrogen steel joints are closely related to the loss of N. The present invention overcomes the nitrogen loss phenomenon during the brazing process of high nitrogen steel, thereby avoiding the occurrence of a large number of air inclusion defects and significantly improving the welding quality of Ti2AlNb / high nitrogen steel.

[0042] In the composite brazing material of the present invention, the alloy components and Ti powder are laid and assembled separately, and the Ti powder laid preferentially controls most of the Ti element on the steel side first, so that it participates in the formation of N compounds in the high nitrogen steel. On the one hand, Ti can fix the N element in the high nitrogen steel, generate TiN strengthening phase, refine the grains of the phase structure, and improve the interface strength, thus overcoming the technical problem of nitrogen loss in high nitrogen steel welding. On the other hand, the TiN continuous strengthening phase layer preferentially generated on the steel side can prevent the Fe element from diffusing into the brazing seam, and inhibit the formation of FeTi brittle intermetallic compounds.

[0043] The brazing process of the present invention is carried out in a vacuum environment, which can prevent the base material titanium alloy from absorbing hydrogen, oxygen and nitrogen at high temperatures, thereby avoiding defects such as embrittlement, pores, inclusions, etc. caused by absorbing a large amount of gas in the brazing seam area.

[0044] The composite solder of the present invention can realize heterogeneous connection of Ti2AlNb / high nitrogen steel. During the brazing process, the Ti element in the Ti2AlNb parent material will diffuse into the brazing seam as the brazing temperature increases. The diffused Ti is equivalent to the supplement of the laid Ti, accelerating the formation of a continuous TiN strengthening phase on the steel side. It is particularly suitable for the connection of Ti2AlNb / high nitrogen steel in the shaft end parts of aircraft engines and the rotor shaft of turbochargers.

[0045] The composite solder of the invention does not contain precious metals such as Au and Ag, has good economic and practical value, has a simple preparation process, and is green and environmentally friendly.

[0046] <Example 1> The composite solder of this embodiment is composed of the following components in mass percentage: 20% Zr2Ni alloy powder, 30% Zr2Cu alloy powder and 50% Ti powder. The particle size of the Zr2Ni alloy powder, Zr2Cu alloy powder and Ti powder is 50 μm.

[0047] The brazing method of this embodiment is as follows: The Ti2AlNb alloy base material and the high nitrogen steel base material were polished with 400-1500# metallographic sandpaper in turn until the surface was bright to obtain the base materials.

[0048] Among them, the chemical composition of high nitrogen steel is as follows (weight percentage): C: 0.01%; Mn: 21.58%; Cr: 18.48%; Ni: 1.46%; Mo: 0.65%; N: 0.86%; Fe: 56.95% and the balance are inevitable impurities.

[0049] The polished base material was immersed in acetone and ultrasonically cleaned for 10 min, then rinsed with anhydrous ethanol and air-dried to obtain the base material to be welded.

[0050] Lay the Ti powder in the composite brazing material on the surface to be welded of the high nitrogen steel base material. The specific method is: select a foil with a pre-laid thickness, leave a laying hole in the middle of the foil, place the foil on the surface to be welded of the high nitrogen steel base material, fill the laying hole with Ti powder, and then gently scrape it flat with a scraper.

[0051] A paste solder is applied on the surface to be welded of the Ti2AlNb alloy base material (the volume ratio of alloy powder to binder in the paste solder is 9:1, and the alloy powder is Zr2Ni alloy powder and Zr2Cu alloy powder in the composite solder), and the surfaces to be welded of the Ti2AlNb alloy base material and the high nitrogen steel base material are relatively fitted together to obtain a pre-brazed assembly.

[0052] Place the pre-brazed assembly in a vacuum furnace and control the vacuum degree to 1.0×10 -3Pa, heating rate is 30℃ / min, heating to 500℃, holding time is 5min, then controlling heating rate to 15℃ / min, heating to brazing temperature of 950℃, holding time is 10min, and brazing connection is performed. After brazing, the sample is cooled to room temperature with the furnace, and the Ti2AlNb / high nitrogen steel brazing connection is completed.

[0053] The preparation process of Zr2Ni alloy powder and Zr2Cu alloy powder in the composite solder is as follows: The Zr2Ni and Zr2Cu alloy foils were crushed and placed in a quartz tube and evacuated to 1×10 -1 MPa and filled with nitrogen; Arc melting is performed until the foil in the quartz tube is completely melted to form a refined melt.

[0054] The refined melt passes through a gas nozzle, solidifies in an atomizing tower, and is transported through a conveying pipe to a cyclone separator to separate coarse powder into fine powder.

[0055] The vacuum atomization method uses QEIGA-50 electrode induction inert gas atomization powder making equipment, with a nozzle diameter of 5 mm, an atomization nozzle diameter of 1 mm, an atomization time of 20 min, and an atomization tower vacuum leakage rate of 0.6 Pa / h.

[0056] Figure 1 The microstructure of the composite solder of this embodiment is as follows: Figure 1 It can be determined that the solder has high sphericity, with the characteristics of fully dense particles and no hollow powder.

[0057] Figure 2 is the DSC test curve of the composite solder of this embodiment, Figure 2 It can be determined that the solidus temperature of the solder is 841.5°C, the liquidus temperature is 847.3°C, and the melting temperature range of the solder is 5.8°C. Within this temperature range, the solder presents a semi-solid state, that is, liquid and solid coexist.

[0058] Figure 3 The microstructure of the brazing seam in this example is shown in Figure 2. The brazing seam is divided into four regions by combining EDS point scanning and surface scanning. The structure is "HNS / TiN / (Ti,Zr)2(Cu,Ni)+Ti(s,s) / B2+O+Ti(s,s) / Ti2AlNb".

[0059] As shown in the following table, it is the quantitative analysis result of EDS point scanning elements on the brazing seam steel side: point Ti Zr Cu Ni Fe Mn Cr N Al Nb phase of matter A 39.06 16.16 3.60 3.12 11.46 4.47 5.73 16.40 / / TiN B 33.88 37.60 13.00 11.77 0.40 0.39 / / 0.67 / <![CDATA[(TiZr)2(CuNi)]]> C 58.81 16.49 6.94 6.98 / / / / 1.07 5.79 <![CDATA[(TiZr)2(CuNi)+Ti(s,s)]]> D 51.09 22.35 3.53 1.00 / / / / 2.76 15.94 <![CDATA[(TiZr)2(CuNi)]]> E 57.64 11.44 2.49 0.77 0.37 0.33 0.33 / 3.25 23.39 B2+O F 70.15 12.32 1.57 0.77 / / / / 1.36 9.93 B2+O G 53.27 / / / / / / / 11.81 26.68 B2+Ti(s,s) H 42.95 / / / / / / / 8.34 39.76 B2+O I 53.06 / / / / / / / 10.31 25.62 <![CDATA[α2+O]]>

[0060] Depend on Figure 3It can be seen that the brazing seam structure is evenly distributed, and no large brittle compounds are generated. Combined with the above table, it can be seen that on the steel side, the Ti powder that is preferentially laid, supplemented by the Ti element diffused in the Ti2AlNb base material, generates a continuous TiN strengthening phase layer with Fe in the steel. This reaction layer prevents the diffusion of Fe elements in the steel into the brazing seam, inhibits the generation of TiFe brittle intermetallic compounds, and improves the quality of the brazing seam.

[0061] Figure 4 Shear fracture of the brazed Ti2AlNb / high nitrogen steel joint (steel side) Figure 4 It can be seen that the uniformly distributed Ti solid solution in the brazing seam improves the toughness of the joint, making the joint present a mixed brittle and tough fracture mode.

[0062] <Example 2> The composite solder of this embodiment is composed of the following components in percentage by mass: 30% Zr2Ni alloy powder, 20% Zr2Cu alloy powder and 50% Ti powder. The particle size of the Zr2Ni alloy powder, Zr2Cu alloy powder and Ti powder are all 10 μm.

[0063] The brazing method of this embodiment is as follows: The Ti2AlNb alloy base material and the high nitrogen steel base material were polished with 400-1500# metallographic sandpaper in turn until the surface was bright to obtain the base materials.

[0064] Among them, the chemical composition of high nitrogen steel is as follows (weight percentage): C: 0.01%; Mn: 21.58%; Cr: 18.48%; Ni: 1.51%; Mo: 0.65%; N: 0.79%; Fe: 56.97% and the balance are inevitable impurities.

[0065] The polished base material was immersed in acetone and ultrasonically cleaned for 12 min, then rinsed with anhydrous ethanol and air-dried to obtain the base material to be welded.

[0066] Lay the Ti powder in the composite solder on the surface to be welded of the high nitrogen steel base material.

[0067] A paste solder is applied on the surface to be welded of the Ti2AlNb alloy base material (the volume ratio of alloy powder to binder in the paste solder is 9:1, and the alloy powder is Zr2Ni alloy powder and Zr2Cu alloy powder in the composite solder), and the surfaces to be welded of the Ti2AlNb alloy base material and the high nitrogen steel base material are relatively fitted together to obtain a pre-brazed assembly.

[0068] Place the pre-brazed assembly in a vacuum furnace and control the vacuum degree to 1.0×10 -3Pa, heating rate is 10℃ / min, heating to 300℃, holding time is 10min, then controlling heating rate to 15℃ / min, heating to brazing temperature of 920℃, holding time is 15min, and brazing connection is performed. After brazing, the sample is cooled to room temperature with the furnace, and the Ti2AlNb / high nitrogen steel brazing connection is completed.

[0069] The preparation process of Zr2Ni alloy powder and Zr2Cu alloy powder in the composite solder is as follows: The Zr2Ni and Zr2Cu alloy foils were crushed and placed in a quartz tube and evacuated to 1×10 -1 MPa and filled with protective gas (nitrogen or argon).

[0070] Arc melting is performed until the foil in the quartz tube is completely melted to form a refined melt.

[0071] The refined melt passes through a gas nozzle, solidifies in an atomizing tower, and is transported through a conveying pipe to a cyclone separator to separate coarse powder into fine powder.

[0072] The vacuum atomization method uses QEIGA-50 electrode induction inert gas atomization powder making equipment, with a nozzle diameter of 5 mm, an atomization nozzle diameter of 1 mm, an atomization time of 15 min, and an atomization tower vacuum leakage rate of 0.5 Pa / h.

[0073] <Example 3> The composite solder of this embodiment is composed of the following components in percentage by mass: 25% Zr2Ni alloy powder, 25% Zr2Cu alloy powder and 50% Ti powder. The particle sizes of the Zr2Ni alloy powder, Zr2Cu alloy powder and Ti powder are all 25 μm.

[0074] The brazing process of this embodiment is as follows: The Ti2AlNb alloy base material and the high nitrogen steel base material were polished with 400-1500# metallographic sandpaper in turn until the surface was bright to obtain the base materials.

[0075] Among them, the chemical composition of high nitrogen steel is as follows (weight percentage): C: 0.01%; Mn: 21.58%; Cr: 18.48%; Ni: 1.51%; Mo: 0.65%; N: 0.79%; Fe: 56.97% and the balance are inevitable impurities.

[0076] The polished base material was immersed in acetone and ultrasonically cleaned for 12 min, then rinsed with anhydrous ethanol and air-dried to obtain the base material to be welded.

[0077] Lay the Ti powder in the composite solder on the surface to be welded of the high nitrogen steel base material.

[0078] A paste solder is applied on the surface to be welded of the Ti2AlNb alloy base material (the volume ratio of alloy powder to binder in the paste solder is 9:1, and the alloy powder is Zr2Ni alloy powder and Zr2Cu alloy powder in the composite solder), and the surfaces to be welded of the Ti2AlNb alloy base material and the high nitrogen steel base material are relatively fitted together to obtain a pre-brazed assembly.

[0079] Place the pre-brazed assembly in a vacuum furnace and control the vacuum degree to 1.0×10 -3 Pa, heating rate is 20℃ / min, heating to 400℃, holding time is 8min, then controlling heating rate to 15℃ / min, heating to brazing temperature of 960℃, holding time is 11min, and brazing connection is performed. After brazing, the sample is cooled to room temperature with the furnace, and the Ti2AlNb / high nitrogen steel brazing connection is completed.

[0080] The preparation process of Zr2Ni alloy powder and Zr2Cu alloy powder in the composite solder is as follows: The Zr2Ni and Zr2Cu alloy foils were crushed and placed in a quartz tube and evacuated to 1×10 -1 MPa and filled with protective gas (nitrogen or argon).

[0081] Arc melting is performed until the foil in the quartz tube is completely melted to form a refined melt.

[0082] The refined melt passes through a gas nozzle, solidifies in an atomizing tower, and is transported through a conveying pipe to a cyclone separator to separate coarse powder into fine powder.

[0083] The vacuum atomization method uses QEIGA-50 electrode induction inert gas atomization powder making equipment, with a nozzle diameter of 5 mm, an atomization nozzle diameter of 1 mm, an atomization time of 18 min, and an atomization tower vacuum leakage rate of 0.55 Pa / h.

[0084] <Example 4-5> Embodiment 4-5 is substantially the same as embodiment 1, except that the brazing temperature is adjusted to 940°C and 960°C.

[0085] <Comparative Example 1> In this comparative example, amorphous foil brazing filler metal for brazing TiAl and 40Cr stainless steel is used instead of the composite brazing filler metal. The rest is the same as in Example 1. The amorphous foil brazing filler metal is composed of the following components in percentage by mass: Ti60%, Zr8%, Cu10% and Ni22%. The preparation method is to vacuum melt the single elements and then make the amorphous foil brazing filler metal by a single-roller strip spinning method.

[0086] <Comparative Example 2> In this comparative example, amorphous foil brazing filler metal is used to replace the composite brazing filler metal for brazing titanium and high nitrogen steel, and the other parts are basically the same as those in Example 1. The amorphous foil brazing filler metal is composed of the following components in mass percentage: Ti37.5%, Zr37.5%, Cu15% and Ni10%. The preparation method is to vacuum melt the single elements and then make the amorphous foil brazing filler metal by a single roller strip spinning method. During the brazing process, the high nitrogen steel is placed at the bottom, the amorphous foil brazing filler metal is placed on the surface to be welded of the high nitrogen steel, and then Ti powder is evenly applied on the amorphous foil brazing filler metal, and finally the Ti2AlNb base material is placed at the top.

[0087] <Comparative Example 3> In this comparative example, amorphous foil brazing filler metal is used instead of composite brazing filler metal for brazing titanium and high nitrogen steel. The other parts are basically the same as in Example 1. The amorphous foil brazing filler metal is composed of the following components in percentage by mass: Ti37.5%, Zr37.5%, Cu15% and Ni10%, and is prepared by single-roller strip spinning followed by vacuum atomization.

[0088] The bonding strength of the brazing Ti2AlNb / high nitrogen steel materials of <Example 1 / 2 / 4 / 5> and <Comparative Example 1 / 2> was tested by a mechanical testing machine. The results are shown in the following table: Group Shear Strength Example 1 312.7MPa Example 2 213.5MPa Example 4 237.9MPa Example 5 228.1MPa Comparative Example 1 29MPa Comparative Example 2 143.1MPa Comparative Example 3 136.5MPa

[0089] From the data in the above table, we can see that:

[0090] 1. When the composite brazing material of the present invention is used for Ti2AlNb / high nitrogen steel brazing, the optimal brazing temperature is 950°C.

[0091] 2. The composite material and brazing method of the present invention are used for brazing connection of Ti2AlNb / high nitrogen steel, and the bonding strength is significantly improved compared with other existing brazing materials. The inventor analyzed that this is because the composite brazing material of the present invention gradually becomes molten as the temperature rises. At this time, two reactions are carried out simultaneously. One is that the N element in the high nitrogen steel reacts with Ti to generate discontinuous and fine TiN strengthening phases. The Ti here only comes from the Ti powder that is preferentially laid on the steel side during the brazing assembly process; the second is that Zr in the Zr2(Cu, Ni) phase formed by the molten alloy powder generates a large amount of (Ti, Zr)2(Cu, Ni) phase under the substitutional solid solution of Ti. The Ti here is the diffused Ti in Ti2AlNb on the one hand, and the laid Ti powder on the other hand is the laid Ti away from one end of the steel side. With the extension of the insulation time, the diffusion of Ti becomes more, and more diffused Ti participates in the Zr2(Cu, Ni) phase change. This process will keep a large amount of laid Ti on the steel side, continue to participate in the generation of fine TiN strengthening phases, and accelerate more TiN crystal nucleation. As the reaction proceeds, a layer of continuous TiN strengthening phase is eventually generated on the steel side surface, which refines the grains of the phase structure and thereby improves the strength of the welding interface.

[0092] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel, characterized in that: The composite solder is composed of 20-30% of Zr2Ni alloy powder, 20-30% of Zr2Cu alloy powder and the remainder of Ti powder in terms of mass percentage.

2. A composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel as claimed in claim 1, characterized in that: The particle sizes of the Zr2Ni alloy powder, Zr2Cu alloy powder and Ti powder are all 10-50 μm.

3. A composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel as claimed in claim 1, characterized in that: The preparation method of the Zr2Ni alloy powder and the Zr2Cu alloy powder is as follows: The alloy foil strip is vacuum melted in an argon atmosphere to obtain an alloy ingot; The alloy ingot is subjected to amorphous forming treatment by a single-roller strip spinning method to obtain amorphous foil strip brazing material; The amorphous foil solder is powdered by vacuum atomization.

4. A composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel as claimed in claim 3, characterized in that: The vacuum atomization method is specifically: The amorphous foil brazing material was crushed and placed in a quartz tube and evacuated to 1×10 -1 MPa and filled with argon; Arc melting is performed to heat the foil strip in the quartz tube until it is completely melted to form a refined melt; The refined melt is solidified into particles in the atomizing tower through a gas nozzle and then sorted through a cyclone separator.

5. A composite brazing filler metal for brazing Ti2AlNb alloy and high nitrogen steel as claimed in claim 4, characterized in that: The diameter of the gas nozzle is 5 mm, the diameter of the atomizing nozzle is 1 mm, the atomizing time is 15~20 min, and the vacuum leakage rate of the atomizing tower is 0.5~0.6 Pa / h.

6. A method for brazing Ti2AlNb alloy and high nitrogen steel using the composite brazing filler metal according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: pre-treating Ti2AlNb alloy base material and high nitrogen steel base material; S2: Spreading Ti powder in the composite brazing filler metal on the surface to be welded of the high nitrogen steel base material, applying paste brazing filler metal on the surface to be welded of the Ti2AlNb alloy base material, and fitting the surfaces to be welded of the Ti2AlNb alloy base material and the high nitrogen steel base material relatively to obtain a pre-brazed assembly; The paste solder is a mixture of Zr2Ni alloy powder, Zr2Cu alloy powder and a binder; S3: Place the pre-brazed assembly in a vacuum brazing furnace at a vacuum degree of 1.0×10 -3 Pa, heat to 300-500°C at a heating rate of 10°C / min-30°C / min and keep warm for 5-10 min, then heat to brazing temperature at a heating rate of 15°C / min and keep warm for 10-15 min for brazing. After brazing, cool to room temperature with the furnace to complete the brazing connection of Ti2AlNb alloy and high nitrogen steel.

7. A brazing method for Ti2AlNb alloy and high nitrogen steel as claimed in claim 6, characterized in that: The step S1 specifically comprises: polishing the welding surfaces of the high nitrogen steel base material and the Ti2AlNb alloy base material with 400#, 900# and 1500# sandpapers in turn, then immersing the polished base materials in acetone for ultrasonic cleaning for 8min to 12min, and finally rinsing with anhydrous ethanol and air-drying.

8. A brazing method for Ti2AlNb alloy and high nitrogen steel as claimed in claim 6, characterized in that: In the step S2, the thickness of Ti powder laid on the surface to be welded of the high nitrogen steel base material is 10-50 μm.

9. A brazing method for Ti2AlNb alloy and high nitrogen steel as claimed in claim 6, characterized in that: The volume ratio of the alloy powder to the binder in the paste solder is 9:

1.

10. A brazing method for Ti2AlNb alloy and high nitrogen steel as claimed in claim 6, characterized in that: The brazing temperature in step S3 is 920°C-960°C.

Citation Information

Patent Citations

  • Strip-shaped brazing filler metal for titanium alloy brazing and Ti2AlNb alloy brazing, preparation method thereof and brazing method

    CN103567666A

  • Brazing material for joining, and composite member and cutting tool using same

    CN105848821A

  • Ti-Zr-Cu-Ni-Re based brazing filler metal for brazing titanium alloy

    CN106271213A

  • Titanium and zirconium-based amorphous alloy brazing filler metal with low contents of Cu and Ni and without containing Si element and preparation method thereof

    CN106392363A

  • Preparation method for titanium-based amorphous brazing filler metal and application in connection of TC4 titanium alloy and 304 stainless steel

    CN108340093A